Contribution to analysis of time courses of soil radon concentration (years 1997–1998) - MOJZEŠ, Andrej (Contributions to Geophysics and Geodesy, 2021)
The article is devoted to the evaluation of the dependence between measured values of 222Rn and 220Rn activity concentration in soil air and some meteorological parameters (temperature, humidity and pressure of atmospheric air) in an annual cycle from 5.3.1997 to 14.12.1998. In addition to year-around assessment of observed dependencies by means of linear regression (Table 1) a more detailed statistical analysis of the variability of daily (weekly) measurements is also presented. Based on these results several shorter time periods (seasons) are detached within a year, which differ from each other by weather character, and during which single meteorological parameters get determining influence on measured concentrations of 222Rn and 220Rn (Table 2). The results document a tight dependence between radon content in pore space of soil cover and meteorological parameters of atmospheric environment in dependence on weather changes in a year cycle.